The Address of Cardinal Stanislaw Dziwisz on the Christian-Jewish Relations - Dziwisz, Cardinal Stanisław (Horyzonty Wychowania, 2009)
Rabbi Rosen, Ladies and Gentlemen, Dear Brothers and Sisters, We are the children of one Father It is with great joy that I have accepted the invitation to speak during this conference which has seen so many people come to Krakow from various corners of the world – people committed to the dialogue, which began at the Second Vatican Council greatly changing the mutual relationships between Christians and Jews. I have come here to thank you for your continuing and courageous following the hard path of dialogue. It is also to assure you how much I personally share your desire that the relations between Christians and Jews become increasingly fruitful as befits the children of One Father, the God of Abraham, Isaac and Jacob.